Xây dựng mô hình kinh tế tổng hợp nuôi Bà-Gà-Trùn đất ở tỉnh Bạc Liêu - Nguyễn, Xuân Khoa (2011)
Tác giả: Nguyễn Xuân Khoa, TS; Trịnh Nguyễn Công Minh, KTV; Châu Thanh Liêm, KS; Châu Đồng Linh, KS -- Từ khóa: Bò; Gà; Giun đất; Trùn đất